Design and Dynamics Performance Simulation Analysis of a New Series Elastic Actuator - Wang Caidong; Wang Yichen; Zhu Jianxin; Hu Yakai; Liu Xiaoli; Dong Xiangsheng; Wang Xinjie (Jixie chuandong)
In order to improve the motion performance of compliant robots, a rotary series elastic actuator (SEA) based on arc helical springs is designed. The proposed SEA can be used to provide a wide range of flexible torsion by the combination of multi-stage rotary structures. The inner and outer double layers of springs with different stiffness are connected in series. The dynamic model of the flexible joint with the proposed SEA is established. The control law for the flexible joint is derived by the backstepping algorithm. To validate the effectiveness of the proposed SEA and the control law, the dynamic performance of the flexible joint with interference torques is simulated by Matlab and Adams. The results show that the controller can overcome the interference force and restore the balance state of the flexible joint within 0.59 s，which verifies the effectiveness of the designed elastic actuator structure and control law.